Imaging of Septo-Optic Dysplasia with Focal Pachygyria: A Case Report (Nepalese Journal of Radiology, 2025)
Septo-optic dysplasia (SOD) is a rare congenital disorder involving the brain and optic pathways. The syndrome is characterized by optic nerve hypoplasia, hypothalamic-pituitary dysfunction, and midline brain defects such as the absence of the septum pellucidum and/or thinning or agenesis of the corpus callosum. Here, we present a case of a 19-year-old female who underwent brain imaging for diminished vision in both eyes since childhood and was diagnosed with SOD. Early clinical suspicion and proper radiological imaging are crucial for the timely diagnosis and management of these patients.